2002
DOI: 10.1176/appi.ajp.159.7.1183
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Premorbid Cognitive Functioning in Patients With Schizophrenia Through Examination of Standardized Scholastic Test Performance

Abstract: Scholastic test scores at grades 4 and 8 were nonsignificantly below average in this group of children who later developed schizophrenia. However, test scores dropped significantly between grades 8 and 11. This corresponds to ages 13-16 years, or the onset of puberty. Poor or declining scholastic performance may be a precursor to the cognitive impairment seen during the first episode of illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
202
3
10

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(230 citation statements)
references
References 25 publications
15
202
3
10
Order By: Relevance
“…These types of analyses will need to be completed on other diagnostic groups to compare the prevalence of cognitive impairment relative to expectations between patients with schizophrenia and other diagnoses. (31,32). However, individuals who will eventually develop schizophrenia also demonstrate decline on scholastic measures between early childhood and late adolescence (32).…”
Section: Prevalence Of Cognitive Impairment In Schizophrenia Versus Omentioning
confidence: 99%
“…These types of analyses will need to be completed on other diagnostic groups to compare the prevalence of cognitive impairment relative to expectations between patients with schizophrenia and other diagnoses. (31,32). However, individuals who will eventually develop schizophrenia also demonstrate decline on scholastic measures between early childhood and late adolescence (32).…”
Section: Prevalence Of Cognitive Impairment In Schizophrenia Versus Omentioning
confidence: 99%
“…In the Philadelphia cohort of the National Collaborative Perinatal Project (Rosso et al, 2000) deviance on motor coordination at age 7 as well as unusual movements at ages 4 and 7 predicted adult schizophrenia, but there was no additional predictive value from assessments of motor functioning later in childhood (teenage years). In a prospective longitudinal study in Iowa, test scores in preschizophrenic children dropped significantly between ages 13-16 years (Fuller et al, 2002). Persistent, pan-developmental (neuromotor, language, cognition) impairment specifically associated with schizophreniform disorder was detected in early childhood in the Dunedin Multidiscliplinary Health and Developmental Survey (Cannon et al, 2002) where cases performed worse than controls on standard tests of motor skill at ages 3, 5, and 9 years but not at age 7 years.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies of premorbid function have revealed abnormalities or developmental delays in neuromotor, cognitive, language, emotional or social functioning. (McNeil et al, 2000;Isohanni et al, 2000a;Jones, 2001;Fuller et al, 2002;Cannon et al, 2003). Jones et al (1994) studied the British 1946 birth cohort and found evidence of delayed motor and speech development by the age of 2 years in those children who developed schizophrenia as adults.…”
Section: Introductionmentioning
confidence: 99%
“…Neurocognitive deficits are persistent characteristics of schizophrenia throughout the illness and are predictors of level of functioning (Green, 1996;Bora et al 2010;Kahn & Keefe, 2013). Several studies have provided evidence indicating that cognitive and intellectual deficits are evident early in neurodevelopment, well before the onset of psychosis (Fuller et al 2002;Reichenberg et al 2010;Kahn & Keefe, 2013). Evidence also suggests that cognitive deficits are stable at follow-up in both chronic and early years of the illness even though performance of schizophrenia patients might improve less than healthy controls at follow-up (Szöke et al 2008;Bora & Murray, 2013;Hedman et al 2013).…”
Section: Introductionmentioning
confidence: 99%